ANALISIS KEBUTUHAN BAHAN AJAR SEJARAH LOKAL LAMPUNG UNTUK SEKOLAH DASAR - Siska, Yulia (Mimbar Sekolah Dasar, 2015)
The aims of the research are: a). to describe the necessary analysis hand’s book of Lampung local history for elementary school level, and b). to describe the formulation of a local Lampung history hand’s books that has as a base culture. The methodology of the research that used was Research and development that used to get to result in the hand book model that develops is the hands' book oh historical subject, especially the local history for elementary school level that has as a base Lampung culture. From the result of necessary data analysis from interviewed with teachers and student's questionnaire, it can be described the require of hands book exists: tradition, the art of tradition (include: dance, sculpture, and music), historic place, habit and life philosophy, kinship, legend, The government system (kingdom, sultanate), patriot and heroism, language, local historical event of colonialism, local historical event of independence, local historical event after independence, local historical event of contemporary, and Lampung's historiography in media.Keywords: necessary analysis, hand book of Lampung local history, elementary school, base culture.